Food waste to livestock feed: prospects and challenges for swine farming in peri-urban Sri Lanka - Jayathilake, Nilanthi; Aheeyar, Mohamed M. M.; Drechsel, Pay (Springer, 2022)
Using farm animals for their natural capability of “recycling” food waste (FW) that is unfit for direct human consumption can support a circular economy as shown in the case of Sri Lanka’s Western Province. The reuse of organic residues including FW as animal feed is a traditional agricultural practice in Sri Lanka but is less studied within an urban FW context. A survey of piggeries using FW in and around the rapidly urbanizing city of Colombo showed that FW is a major feed source in the farms accounting for on average 82% of total feed. About 40% of the farms collected the FW mainly from hotels, restaurants, and institutional canteens. Urban FW is supplied to farmers free of charge when collected directly from the sources, although 26% of the farmers collected FW via intermediaries against a fee. As FW is collected daily, the restaurants appreciate the reliable service, the farmers the low-cost feed, and the municipality the reduced FW volumes to be collected. However, this triple-win situation encounters challenges such as (tourist related) seasonal low supply, which was exacerbated under the Covid-19 lockdown of food services. Another area of concern refers to biosafety. Although the large majority of interviewed farmers boil FW which contains raw meat or fish, there is a paucity of related guidelines and control. Given the benefits of FW use, it is worthwhile to explore how far these informal partnerships could be scaled without increasing transport costs for farmers, while introducing biosafety monitoring. For now, the regulatory environment is highly siloed and does not support material transitions across sector boundaries towards a circular economy.